Experimental assessment of the liquefaction resistance of calcareous biogenous sands - Sandoval Eimar; Pando Miguel A (Earth Sciences Research Journal)
ABSTRACT Liquefaction is a phenomenon in which soils, typically sands, suddenly loose a substantial amount of their shear strength and stiffness, this often triggered by large-magnitude earthquakes. Most liquefaction research has focused on silicate-based sands and not on other sand types, such as calcareous biogenous sands Calcareous sands are usually composed of skeletal or non-skeletal remains of marine organisms, with unique characteristics in terms of their mineralogy surface roughness, particle shape, crushability, and intraparticle porosity. The unique characteristics of calcareous sands suggest that their geotechnical engineering behaviour can be substantially different compared to that of terrigenous sands, including their behaviour under seismic loading, which have not been very well studied This paper presents the results of an experimental programme aimed at studying the cyclic liquefaction resistance of uncemented calcareous biogenous sands retrieved from south-western Puerto Rico Evaluation of liquefaction potential involved a comprehensive set of isotropically consolidated undrained cyclic triaxial tests on reconstituted samples of this calcareous sand. The programme also included tests on Ottawa terrigenous silica sand samples prepared and tested in similar conditions for comparison purposes. In general, the experimental results showed that Cabo Rojo calcareous sands had higher liquefaction resistance compared to Ottawa silica sands tested under similar conditions. Important differences between calcareous and silica sands regarding pore pressure generation characteristics and axial strain accumulation were also observed RESUMEN La licuación es un fenómeno en el cual los suelos, típicamente arenas, pierden una cantidad importante de su rigidez y resistencia al esfuerzo cortante, generalmente por causa de sismos de gran magnitud . La mayoría de investigaciones sobre licuación se han enfocado en arenas terrígenas con base de sílice o cuarzo, y no sobre otro tipo de arenas, como las arenas calcáreas biogénicas . Las arenas calcáreas están usualmente compuestas por residuos de organismos marinos esqueléticos y no esqueléticos, con características específicas en términos de su mineralogía, rugosidad superficial, forma de partículas, susceptibilidad al rompimiento y porosidad interna de los granos Las características particulares de las arenas calcáreas, hacen suponer que su comportamiento ingenieril geotécnico puede ser considerablemente diferente comparado con el de arenas terrígenas, incluyendo su comportamiento bajo carga sísmica, el cual no ha sido estudiado en detalle Este artículo presenta los resultados de un programa experimental desarrollado con el fin de estudiar la resistencia a licuación cíclica de una arena calcárea biogénica no cementada, extraída del suroeste de Puerto Rico La evaluación del potencial de licuación incluyó una extensa cantidad de ensayos triaxiales cíclicos no drenados consolidados isotrópicamente, sobre muestras no cementadas de esta arena calcárea Para fines de comparación, el programa también incluyó ensayos sobre la arena terrígena de Ottawa bajo condiciones de prueba similares En general, los resultados experimentales mostraron que las arenas calcáreas de Cabo Rojo tuvieron mayor resistencia a licuación, comparada con las arenas de Ottawa para condiciones de prueba similares También se observaron diferencias importantes en cuanto a las características de generación de presiones de poros y acumulación de deformaciones axiales